Breaking the Taboo: Illicit Drug Use among Adolescents with Type 1 Diabetes Mellitus - Anna M. Hogendorf; Wojciech Fendler; Janusz Sieroslawski; Katarzyna Bobeff; Krzysztof Wegrewicz; Kamila I. Malewska; Maciej W. Przudzik; Malgorzata Szmigiero-Kawko; Beata Sztangierska; Malgorzata Mysliwiec; Agnieszka Szadkowska; Wojciech Mlynarski (Journal of Diabetes Research)
Background. The aim of the study was to explore the prevalence of illicit drug use in a group of Polish adolescents with type 1 diabetes (DM1) in comparison with a national cohort of their healthy peers. Methods. Two hundred and nine adolescents with DM1, aged 15–18 years, were studied in 2013 with an anonymous questionnaire prepared for the European School Survey Project on Alcohol and Other Drugs (ESPAD). The control group was a representative sample of 12114 students at the same age who took part in ESPAD in 2011. Metabolic control was regarded as good if self-reported HbA1c was <8% or poor if HbA1c was ≥8%. Results. Lifetime prevalence of illicit drug use was lower among adolescents with DM1 than in the control group [58 (28%) versus 5524 (46%), p=10-5]. Cannabis preparations were the most frequently used substances [38 (18.3%) versus 3976 (33.1%), p=10-5], followed by tranquilizers, sedatives, and amphetamine. Lifetime and last 12-month use of cannabis were associated with poorer glycemic control (HbA1c ≥ 8%), p<0.01 and 0.02, respectively. Conclusions. Adolescents with DM1 report using illicit drugs to a lesser extent than their healthy peers. The use of cannabis is associated with a poorer metabolic control in teens with DM1.